Evaluation of Lentiform Nuclei Volume in Healthy Individuals Who Exercise Regularly Using the Semi-automatic Tracing Technique - Funda Aksu; Selim Karabekir; Nuri Karabay; Erkan Gunay, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study conducted volumetric analyses on the lentiform nuclei, specifically the putamen and globus pallidus, in healthy individuals. The analyses considered age, gender, and body mass index. The measurements were performed separately for each hemisphere. This study aimed to examine potential differences in regular exercising men and women based on age, gender, and body mass index (BMI) through volumetric analysis of lentiform nuclei. A total of 16 individuals (7 female and 9 male) who exercise regularly were randomly selected for this study. The cross-sections were assessed to determine the volumes of the left and right lentiform nuclei in relation to age, gender, and body mass index for each participant. Statistical analysis was performed using the semi-automatic tracking method in MRI. Both genders showed higher left lentiform nuclei volume and putamen volume, while the right globus pallidus volume was also higher. However, these differences were not statistically significant. The volume of the lentiform nuclei was found to be greater in women compared to men, although this difference was not statistically significant. A significant positive correlation was observed between the volume of the right globus pallidus and age in men. A positive correlation was observed between right putamen volume, left lentiform nuclei volume, and left putamen volume with body mass index in all subjects. However, this correlation was not statistically significant. The data may contribute to the creation of a comprehensive database that includes typical lentiform nuclei and potential asymmetrical alterations in brain morphology. Furthermore, it has the potential to offer valuable insights to clinicians and anatomists.